Propuesta de mejora para la evaluación de desempeño del registro de la propiedad del Cantón Bolívar con base al modelo EVAL-01 - Basurto Loor, José Daniel (2018)
The Property Registry of Bolívar canton is an institution attached to the Autonomous Municipal Government of the canton, which must comply with all laws in the different areas that were created for its effect, however this institution has not performed the performance evaluation as establishes the law. To corroborate the information that is handled about the problem that afflicts the institution, instruments were applied for the information gathering which were used in the field investigation, surveys and interviews, while the bibliographical investigation allowed to justify scientifically the research, in addition to the inductive, deductive, analytical and synthetic methods were essential for the processing and incorporation of classified information to the improvement proposal. In the field investigation it was possible to verify that in the Property Registry of the Bolívar canton the performance evaluation has never been carried out, and that the Human Talent Director of this institution, responsible for its application, does not know the procedure of how to fill the fields of the model. This is why the need arises to structure an improvement proposal that includes the procedure to fill each of the fields of the EVAL-01 model, also providing the guidelines and legal basis to consider for compliance.